Personality traits and attitude towards the development of theses seniors psychology at the Universidad Peruana Union - Subsidiary Juliaca. - Mamani Benito, Oscar Javier (2019)
Objective: to determine the relationship between personality traits and attitude towards developing thesis inthe fourth year students of psychology at the Peruvian Union University - Subsidiary Juliaca. Material andMethods: a quantitative approach, no experimental design, cross-sectional, descriptive correlational level. Thepopulation consisted of 39 students. Personality inventory NEO PI-R form S, and a scale of attitude towardsdeveloping thesis was applied. Results: there are correlations between : the trait openness and attitude towardsthe development of thesis (r = 0.537 , p < 0.05) , and between the trait awareness and attitude towards thedevelopment of thesis (r = 510, p < 0.05) ; well no correlation between neuroticism trait and attitude towards thedevelopment of thesis (r = -0.010 , p > 0.05 ) between the extraversion trait and attitude towards the developmentof thesis (r = 0.407 , p > 0.05) were found and between agreeableness trait and attitude towards the developmentof thesis (r = -0.261 , p > 0.05 ).